Welcome to my home: cell block D - White, Regina Lynn (Incarceration and older women, 2023)
This chapter investigates theory and research on the prison experience for men and women. It reviews classic studies of prisonization and coping with the pains of imprisonment. It then attends to studies from feminist perspectives on the circumstances and concerns of women in prison and their strategies for coping. Women’s past domestic violence victimization, drug addiction, and current family responsibilities complicate ‘prison experience’. The latter cannot be understood in a gender-neutral fashion.